Database and WebGIS: tools for integration and access to biodiversity information of invertebrates of the marine reserve 'El Pelado' (REMAPE). Issue 1 (30th November 2018) - Agurto, Gabriela; Andrade, Elizabeth; Tomalá, Cecilia; Domínguez, Cristóbal; Guillén, Paúl; Jaramillo, Karla; Lavorato, Antonella; Condor-Lujan, Báslavi; Chalén, Bolívar; Avellaneda, Karen; Thomas, Olivier; Sonnenholzner, Stanislaus; et al.
ABSTRACT: The marine biodiversity program of CENAIM-ESPOL focuses on sessile invertebrates from the "'El Pelado' marine reserve". The present study aims at understanding the different hierarchical levels of biodiversity found at the "El Pelado" and to guide biodiscovery initiatives. Generated biodiversity data were systematized in a database (Darwin Core standard) and integrated into a geographic information system that uses webGIS as a search engine. In this way, the information becomes available to the academy and entities involved in the management of coastal resources.